Inhibition of the metabolism of mixed cultures of purple phototrophic bacteria by typical refinery and petrochemistry wastewater pollutants. Issue 7 (19th March 2021) - San Martín, Javier; Puyol, Daniel; Melero, Juan A; Segura, Yolanda; Martínez, Fernando
Abstract: BACKGROUND: Anaerobic treatments based on purple phototrophic bacteria (PPB) can be a more efficient and less energetically demanding alternative to aerobic biological processes currently used in refinery and petrochemistry wastewater (RPWW) treatment plants. Toxic compounds in the RPWW might compromise PPB metabolism, limiting its feasibility. In this work, seven toxic compounds that are typical components of RPWW [benzene, toluene, ethylbenzene, o ‐xylene (BTEX), furfural, methyl‐di‐ethanolamine (MDEA) and butanone] were evaluated as potential inhibitors of the specific activity and growth of PPB. RESULTS: Inhibitory K i parameters of 50% reduction of specific activity or biomass yield were calculated. Most of the BTEX compounds showed initial inhibitory effects on the specific activity, with K i values of 305 ± 9, 151 ± 17 and 84 ± 2 mg L −1 for benzene, toluene and ethylbenzene, respectively. These compounds also caused inhibition of PPB growth ( K i of 411 ± 7 and 241 ± 3 mg L −1, 26% below the control, respectively). By contrast, o ‐xylene affected neither the activity nor the growth. Furfural inhibited the initial specific activity ( K i of 448 ± 24 mg L −1 ), with no effect over the PPB growth. However, MDEA and butanone improved the initial specific activity of PPB (15% and 40% above the control, respectively). However, butanone negatively impacted the growth which decreased to ≤40% below the control. CONCLUSIONS: Calculated inhibition thresholds for the seven toxic compounds were far above the actual concentrations found in the RPWW. Thus, anaerobic treatments based on PPB for the treatment of RPWW would not be limited by the presence of the toxic compounds studied here. © 2021 Society of Chemical Industry (SCI).